First principles study of the structural, stability properties and lattice thermal conductivity of bulk ReSe2. (2018) - Mahmoud, Mahmoud M.A.; Joubert, Daniel P.
Abstract: Thermoelectric devices can convert heat into an electric current and have immense potential for efficient use of the available energy. This includes converting heat energy from internal combustion engines, conventional power plants and solar cells into usable energy. Research into finding efficient thermoelectric materials has intensified over the past decade. One of the desired features of efficient thermoelectric materials is a low lattice thermal conductivity. In other words, the thermal energy transported by the motion of the atoms in thermoelectric materials should be small. Recent research suggests that some layered materials may possess this property. In this study we used first-principles calculations to investigate the structural, mechanical, and vibrational properties of bulk ReSe2, a layered material. The lattice thermal conductivity was calculated by using a single-mode relaxation-time approximation in the linearized phonon Boltzmann equation from first-principles an-harmonic lattice dynamics calculations. We find that the lattice thermal conductivity of ReSe2 is non-isotropic, with the highest value of 18.58 W ( mK ) - 1 along the a-axis and lowest one of 0.69 W ( mK ) - 1 along the c-axis at room temperature. These values make this an interesting material as a potential active component in a thermoelectric device.